Mon2-monocytes and increased CD-11b expression before transcatheter aortic valve implantation are associated with earlier death. (1st November 2020) - Pfluecke, C.; Wydra, S.; Berndt, K.; Tarnowski, D.; Cybularz, M.; Jellinghaus, S.; Mierke, J.; Ende, G.; Poitz, D.M.; Barthel, P.; Heidrich, F.M.; Quick, S.; et al.
Abstract: Background: In the first three months after Transcatheter aortic valve implantation (TAVI), a remarkable number of patients have an unfavorable outcome. An inflammatory response after TAVI is suspected to have negative effects. The exact mechanisms remain unclear. We examined the influence of monocyte subpopulations on the clinical outcome, along with the degree of monocyte activation and further parameters of inflammation and platelet activation. Methods: Flow-cytometric quantification analyses of peripheral blood were done in 120 consecutive patients who underwent TAVI (one day before TAVI and on day 1 and 7 after TAVI). Monocyte-subsets were defined by their CD14 and CD16 expression, monocyte-platelet-aggregates (MPA) by CD14/CD41 co-expression. The extent of monocyte activation was determined by quantification of CD11b-expression (activation epitope). Additionally, pro-inflammatory cytokines such as interleukin (IL)-6, IL-8, C-reactive protein were measured with the cytometric bead array method or standard laboratory tests. Results: Elevated Mon2 (CD14 ++ CD16 + ) - monocytes (38 vs. 62 cells/μl, p < 0.001) and a high expression of CD11b prior to TAVI (MFI 50.1 vs. 84.6, p < 0.05) were independently associated with death 3 months after TAVI. Mon2 showed the highest CD11b-expression and CD11b correlated with platelet activation and markers of systemic inflammation. Even CRP and IL-8 before TAVI were associated with death after TAVI. In contrast, a systemic inflammation response shortly after TAVI was not associated with early death. Conclusions: Elevated Mon2-monocytes and a high level of monocyte activation before TAVI are associated with early mortality after TAVI. Chronic inflammation in aging patients seems to be an important risk factor after TAVI. Highlights: An elevated content of Mon2 monocytes are associated with death after TAVI. CD11b-expression on monocytes, as sign of enhanced cellular activity before TAVI, are associated with death after TAVI as well. Mon2 and CD11b before TAVI may disclose a use as biomarkers and function as possible therapeutic targets in the future. A systemic inflammatory response shortly after TAVI was not associated with worse outcome. The kind of inflammation and the involved cells rather than the extent itself determines the survival after TAVI.